2011
DOI: 10.1007/s10308-011-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants and risk factors for non-communicable diseases (NCDs) in South Asian migrant populations in Europe

Abstract: In Europe, policies, strategies and interventions to address the growing burden of non-communicable diseases have generally neglected to take into consideration the impact of migration on health outcomes of increasingly multicultural and diverse societies. Research has shown that migrants of South Asian origin living in Europe are more at risk of acquiring non-communicable diseases than their counterparts in their country of origin or than the host European population. Using the example of migrants of South As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Ethnic minority groups, women, and those of lower socioeconomic status in the UK are known to have higher morbidity and premature mortality from CVD [ 7 ] and other chronic diseases than white European populations [ 7 ]. SA women in the UK are a group known to be affected by all of these factors [ 3 , 8 ]. In the UK, 33% of all mortality in SA in 2008 was caused by CVD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minority groups, women, and those of lower socioeconomic status in the UK are known to have higher morbidity and premature mortality from CVD [ 7 ] and other chronic diseases than white European populations [ 7 ]. SA women in the UK are a group known to be affected by all of these factors [ 3 , 8 ]. In the UK, 33% of all mortality in SA in 2008 was caused by CVD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AIPA population is at increased risk for cancer and other preventable diseases due to the effect of migration on lifestyle and sociocultural determinants of health. 4 The incidence of breast cancer, which is amenable to screening and early detection, is increasing among AIPA women. 5 Few studies have examined the characteristics of breast tumors in AIPA.…”
mentioning
confidence: 99%
“…Its weakness as a predictor of insulin resistance, T2DM and CVD risk factors in South Asians and their migrant compatriots has been well documented [2,27,36,38]. Higher centripetal fat among South Asians is associated with higher susceptibility to NCDs at a BMI ≤ 30 kg/m 2 [24]. Those with a 'normal' BMI, but large WC, may have a two-to threefold higher risk of CVD and premature death [35].…”
Section: Anthropometrymentioning
confidence: 99%
“…Although several authors have documented health inequalities among ethnic minorities, further understanding is needed concerning the interplay of biological, genetic, developmental, socioeconomic, demographic, religious, cultural and behavioural factors [21][22][23][24][25][26][27]. For example, Higgins et al demonstrated a strong association between waist circumference (WC) and ethnicity in the UK, with WC increasing in proportion to migrants' length of residence [3].…”
Section: Introductionmentioning
confidence: 99%